Perlindungan Hukum Perawat Dalam Pelayanan Kesehatan Berdasarkan Undang-Undang - Sismulyanto; Wahyati, Endang; Ta’adi; Putra, Made Mahaguna (State Islamic University of Sunan Ampel, 2024)
The administration of anesthesia is a medical procedure fraught with considerable risk. The prevalence of anesthesia-related mortality is often understated, reminiscent of the so-called iceberg phenomenon. On-the-ground realities reveal that due to a shortage of anesthesiologists, nurse anesthetists frequently perform anesthetic procedures under the guidance of anesthesiologists. The annulment of Minister of Health Regulation Number 32 from the year 2013 has resulted in vulnerabilities within the practice of anesthesia nursing. Given the significant consequences associated with anesthetic procedures, it is imperative to have legal safeguards in place for nurse anesthetists. This study utilizes a descriptive-analytical framework and adopts a normative juridical approach, employing deductive reasoning. The research relies on secondary data, which is qualitative and gathered through a comprehensive review of relevant literature. The study's analytical process makes use of normative qualitative methods. In the context of this study, nurse anesthetists receive their delegated authority from physicians and must operate within the constraints set forth by the Medical Practice Act, Health Personnel Law, and Health Minister Regulations related to medical practice permits. Nurse anesthetists assign their tasks based on authority that is delegated in line with legislation No. 38 from 2014 concerning nursing. The specialist anesthesiologist has both legal and moral responsibility for providing protection to nurses executing tasks under such delegated authority since their duties are performed according to physicians' orders and directives. There exists a pressing need to revisit Ministerial Regulation No. 18 from 2016, concerning the licensing and execution of anesthesia management, in order to clarify the roles and functions proprietary to anesthesiologists as determined by their expertise. It is incumbent upon the Minister of Health to promptly issue new regulations pertaining to nurse anesthesia practice, ensuring that healthcare services are provided without any legal discrepancies.